Studies on the biological oxidation - The oxidation of ascorbic acid (vitamin C) in biological fluids - Guzmán Barrón, E. S. (1936)
Biological fluids can be divided according to their behavior toward ascorbic acid into two groups: those having an inhibitory mechanism that protects the ascorbic acid oxidation, and those lacking this mechanism. Animal fluids and some of vegetable origin (those containing dosables amounts of ascorbic acid) corresponding to the first group. Ascorbic acid is protected from oxidation in the fluids by the action of copper catalyst. Fluids from plants (those that contain very little ascorbic acid) belong to the second group. Ascorbic acid is oxidized in these fluids by a variety of oxidizing catalysts, copper and hemocromógenos, as evidenced by the effect of inhibitors. The inhibitory effect of glutaction is specific to the catalytic action of ascorbic acid by hemocromógeno ferri-nicotine or yellow pumpkin juice.